Re-framing teacher evaluation discourse in the media: an analysis and narrative-based proposal. Issue 1 (2nd January 2016) - Ulmer, Jasmine B.
Abstract : Recent publications by major newspapers in the USA have reinforced the perception that teacher quality represents a national crisis. By releasing individual teacher evaluation data in online, searchable databases, several newspapers have influenced public perceptions of teachers and teaching. A framing analysis of selected media events and publications identifies how these media-based actions have created and perpetuated a discourse of professional inadequacy. Rather than envision educators as fixed within media frames, however, the author discusses how practitioners can reinscribe their profession by engaging with the media and the public themselves. In this model, counter-narratives become a means to deconstruct metanarratives, foster complexity, and expand practitioner voice(s). In a turn toward poststructural theory, the author considers how counter-narratives and petit narratives might proliferate across online media into an assemblage of multiplicities that de/reterritorialize educational discourse. Such a reinscription potentially represents a first move in shifting public discourse about teacher quality onto both more nuanced and more productive ground.